Maltese in London, 1966-1969: Court Record Analysis, 1941-1966 - Dench, Geoff (UK Data Service, 1976)
The purpose of this study was to provide some evidence about the overall pattern and trend in Maltese criminality in London, against which arguments about the origin and consequences of the Maltese reputation could be assessed more realistically.